Research on University Library Finance in India - Navalani, K.; Sehgal, P.C. (DESIDOC Journal of Library & Information Technology, 2003)
Education and libraries play a significant role in bringing about qualitative improvements in human resources. Finance plays a vital rde in growth and development of libraries. This article presents statistical data about finances of university libraries of seven states taken from Ph.D theses of library & information science scholars. http://dx.doi.org/10.14429/dbit.18.5.3412